Eufonia połączeń polskich imion i nazwisk = Euphony in Polish combination of first and last names - Ruszkowski, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of analysis in the article is euphony perceived as a pleasant sound, as avoidance of combinations of sounds difficult to pronounce and harmonization of sounds in combinations of first and last names. First name - last surname combinations may be perceived as phonetically harmonious, nice-sounding, euphonic, or as inharmonious sounds, difficult to articulate, or even cacophonous.
Keywords: eufonia; imię; nazwisko; prawo językowe Behaghla; euphony; first name; surname; Behaghel`s linguistic law